2015
DOI: 10.1111/febs.13347
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic formylglycine‐generating enzyme catalyses a monooxygenase type of reaction

Abstract: C a-formylglycine (FGly) is the catalytic residue of sulfatases in eukaryotes. It is generated by a unique post-translational modification catalysed by the FGly-generating enzyme (FGE) in the endoplasmic reticulum. FGE oxidizes a cysteine residue within the conserved CxPxR sequence motif of nascent sulfatase polypeptides to FGly. Here we show that this oxidation is strictly dependent on molecular oxygen (O 2 ) and consumes 1 mol O 2 per mol FGly formed. For maximal activity FGE requires an O 2 concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 28 publications
0
27
0
4
Order By: Relevance
“…The combination of catalytic and structural analyses of FGE described here and elsewhere strongly implicates FGE as a copper‐metalloenzyme: the active form strongly binds one equivalent of Cu I in the active site; the Cu I :protein complex remains intact throughout the entire catalytic cycle (Figure ); other transition metals cannot complement FGE, thus suggesting that the cofactor engages in redox chemistry; FGE reduces O 2 by using two electrons from the substrate and two electrons from an auxiliary reducing agent such as DTT; in the presence of DTT the rate‐limiting step is hydrogen‐atom abstraction from the substrate; the accumulating species during catalysis is an EPR‐silent species (Figure ); in the absence of an appropriate reducing agent turnover is much slower, and a Cu II ‐containing species accumulates (Figure ); this oxidized species can slowly turn over by using the substrate thiol as an electron source; and finally, addition of a proper reducing agent to this slow reaction immediately reactivates the enzyme …”
Section: Methodsmentioning
confidence: 69%
“…The combination of catalytic and structural analyses of FGE described here and elsewhere strongly implicates FGE as a copper‐metalloenzyme: the active form strongly binds one equivalent of Cu I in the active site; the Cu I :protein complex remains intact throughout the entire catalytic cycle (Figure ); other transition metals cannot complement FGE, thus suggesting that the cofactor engages in redox chemistry; FGE reduces O 2 by using two electrons from the substrate and two electrons from an auxiliary reducing agent such as DTT; in the presence of DTT the rate‐limiting step is hydrogen‐atom abstraction from the substrate; the accumulating species during catalysis is an EPR‐silent species (Figure ); in the absence of an appropriate reducing agent turnover is much slower, and a Cu II ‐containing species accumulates (Figure ); this oxidized species can slowly turn over by using the substrate thiol as an electron source; and finally, addition of a proper reducing agent to this slow reaction immediately reactivates the enzyme …”
Section: Methodsmentioning
confidence: 69%
“…[17] This recognition sequence can be introduced into recombinant proteins and converted by FGE in vivo or in vitro. [19][20][21][22] In addition, the iron-sulfur protein AtsB of the radical S-adenosyl methionine (radical-SAM) protein superfamily is another FGly-generating system that is exclusively found in prokaryotes. [19][20][21][22] In addition, the iron-sulfur protein AtsB of the radical S-adenosyl methionine (radical-SAM) protein superfamily is another FGly-generating system that is exclusively found in prokaryotes.…”
mentioning
confidence: 99%
“…Peng et al . correctly point out that their data leave this problem open for further investigation. X‐ray crystallographic studies on human FGE have shown that, upon aging, the crystalline enzyme oxidizes so that the peroxysulfenic form of the catalytic Cys336 (Cys‐S‐O‐O − ) accumulates.…”
mentioning
confidence: 96%
“…In this issue of FEBS Journal , Peng et al . report interesting experimental data that provide insight into the unusual and intriguing FGE‐catalyzed reaction. Their starting point is that FGE enzymatic activity is known to depend on molecular oxygen as a co‐substrate as well as on two essential catalytic residues, Cys336 and Cys341 (with reference to the human FGE sequence).…”
mentioning
confidence: 99%
See 1 more Smart Citation